2004
DOI: 10.1152/ajpheart.00493.2004
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1/A2a receptor agonist AMP-579 induces acute and delayed preconditioning against in vivo myocardial stunning

Abstract: The purpose of this study was to determine whether the adenosine A1/A2a receptor agonist AMP-579 induces acute and delayed preconditioning against in vivo myocardial stunning. Regional stunning was produced by 15 min of coronary artery occlusion and 3 h of reperfusion (RP) in anesthetized open-chest pigs. In acute protection studies, animals were pretreated with saline, low-dose AMP-579 (15 microg/kg iv bolus 10 min before ischemia), or high-dose AMP-579 (50 microg/kg iv at 14 microg/kg bolus + 1.2 microg.kg(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
(48 reference statements)
0
11
0
Order By: Relevance
“…The animal was then euthanized with a pentobarbital overdose, the heart was excised, and the atria and great vessels were removed. The heart was sliced into three to four pieces (Ͼ2 mm thickness) from base to apex for staining with triphenyltetrazolium chloride solution to measure infarct size as previously described (12). The AAR was devoid of Evans blue dye while the infarcted tissue within the AAR was the triphenyltetrazolium chloride -negative stained region.…”
Section: Allmentioning
confidence: 99%
“…The animal was then euthanized with a pentobarbital overdose, the heart was excised, and the atria and great vessels were removed. The heart was sliced into three to four pieces (Ͼ2 mm thickness) from base to apex for staining with triphenyltetrazolium chloride solution to measure infarct size as previously described (12). The AAR was devoid of Evans blue dye while the infarcted tissue within the AAR was the triphenyltetrazolium chloride -negative stained region.…”
Section: Allmentioning
confidence: 99%
“…Treatment with AMP579, both prior to ischemia and during reperfusion, reduces in vivo infarct size in several species [26][27][28][29][30][31], due to its ability to activate both adenosine A 1 and A 2A receptors. We have recently reported that pretreatment with AMP579 dose-dependently attenuated in vivo myocardial stunning, with only minor, transient reductions in HR and MAP [10]. This anti-stunning effect of AMP579 was completely blocked by the adenosine A 1 receptor antagonist DPCPX, indicating that this cardioprotective effect was mediated via A 1 receptor activation.…”
Section: Discussionmentioning
confidence: 91%
“…On the other hand, AMP579 is a unique agent with high affinity for both adenosine A 1 and A 2A receptors, and it has been shown to exert much less hemodynamic effects in vivo [10,[26][27][28][29]. Treatment with AMP579, both prior to ischemia and during reperfusion, reduces in vivo infarct size in several species [26][27][28][29][30][31], due to its ability to activate both adenosine A 1 and A 2A receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations